Activation of Muscarinic Acetylcholine Receptor Subtype 4 Is Essential for Cholinergic Stimulation of Gastric Acid Secretion: Relation to D Cell/Somatostatin - Takeuchi, Koji; Endoh, Takuya; Hayashi, Shusaku; Aihara, Takeshi (Frontiers in Pharmacology, 2016)
Background/Aim: Muscarinic acetylcholine receptors exist in five subtypes (M1∼M5), and they are widely expressed in various tissues to mediate diverse autonomic functions, including gastric secretion. In the present study, we demonstrated, using M1∼M5 KO mice, the importance of M4 receptors in carbachol (CCh) stimulation of acid secretion and investigated how the secretion is modulated by the activation of M4 receptors. Methods: C57BL/6J mice of wild-type (WT) and M1–M5 KO were used. Under urethane anesthesia, acid secretion was measured in the stomach equipped with an acute fistula. CCh (30 μg/kg) was given subcutaneously (s.c.) to stimulate acid secretion. Atropine or octreotide (a somatostatin analog) was given s.c. 20 min before the administration of CCh. CYN154806 (a somatostatin SST2 receptor antagonist) was given i.p. 20 min before the administration of octreotide or CCh. Results: CCh caused an increase of acid secretion in WT mice, and the effect was totally inhibited by prior administration of atropine. The effect of CCh was similarly observed in the animals lacking M1, M2 or M5 receptors but significantly decreased in M3 or M4 KO mice. CYN154806, the SST2 receptor antagonist, dose-dependently and significantly reversed the decreased acid response to CCh in M4 but not M3 KO mice. Octreotide, the somatostatin analog, inhibited the secretion of acid under CCh-stimulated conditions in WT mice. The immunohistochemical study showed the localization of M4 receptors on D cells in the stomach. Serum somatostatin levels in M4 KO mice were higher than WT mice under basal conditions, while those in WT mice were significantly decreased in response to CCh. Conclusions: These results suggest that under cholinergic stimulation the acid secretion is directly mediated by M3 receptors and indirectly modified by M4 receptors. It is assumed that the activation of M4 receptors inhibits the release of somatostatin from D cells and minimizes the acid inhibitory effect of somatostatin through SST2 receptors, resulting in enhancement of the acid response mediated by M3 receptors on parietal cells.